1988
DOI: 10.1002/j.1556-6676.1988.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

The Noncustodial Parent: Dilemmas and Interventions

Abstract: This article focuses on the often overlooked group of people, usually men, who are noncustodial parents. The authors discuss 10 common dilemmas of parents in this position and delineate what can be done by individual and family counselors to enhance the ability of these parents to maintain parenting relationships with their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Noncustodial divorced parents represent another group restrained from interacting with their children. Wilbur and Wilbur (1988) observed that most such parents refused to accept that the bond to their children was severed or even damaged, even when their lawyers advised them to abandon efforts to continue the relationship. Thus, the bond is apparently very important to these parents even if it is mainly associated with frustration, aggravation, and disappointment.…”
Section: Review Of Empirical Findingsmentioning
confidence: 99%
“…Noncustodial divorced parents represent another group restrained from interacting with their children. Wilbur and Wilbur (1988) observed that most such parents refused to accept that the bond to their children was severed or even damaged, even when their lawyers advised them to abandon efforts to continue the relationship. Thus, the bond is apparently very important to these parents even if it is mainly associated with frustration, aggravation, and disappointment.…”
Section: Review Of Empirical Findingsmentioning
confidence: 99%
“…In addition, there is a pervasive perception that nonresident and indeed single parents are less viable in the eyes of society (Wilbur & Wilbur, 1988). Society seems to view an individual's failure to maintain or succeed in her or his primary relationship as a potential failure as a parent.…”
Section: Sociocultural Perspectivementioning
confidence: 99%
“…The roles parents play in their children's lives after the dissolution of their partnership clearly changes. The development of new roles as nonresident parents is challenging enough, but this process is made more difficult by the lack of acceptance by the social system (Wilbur & Wilbur, 1988).…”
Section: Sociocultural Perspectivementioning
confidence: 99%
“…Furthermore, mental health professionals need to be more available to noncustodial fathers. Typically, in dealing with divorced parents or children from divorced families, therapists usually conduct sessions without the parent-usually a noncustodial father-who lives away from the children (Wilbur & Wilbur, 1988). To resolve issues affecting the divorced family, such as disturbances in parent-child relations and problems with visitation, custody, and child support, the entire family system must be considered when developing treatment initiatives.…”
Section: Implications For Policy and Practicementioning
confidence: 99%